Dosimetric Impact of Inter-Fraction Anatomical Changes in Carbon Ion Boost Treatment for High-Risk Prostate Cancer (AIRC IG 14300) - Russo, Stefania; Ricotti, Rosalinda; Molinelli, Silvia; Patti, Filippo; Barcellini, Amelia; Mastella, Edoardo; Pella, Andrea; Paganelli, Chiara; Marvaso, Giulia; Pepa, Matteo; Comi, Stefania; Zaffaroni, Mattia; et al. (Frontiers in Oncology, 2021)
Rectum and bladder volumes play an important role in the dose distribution reproducibility in prostate cancer adenocarcinoma (PCa) radiotherapy, especially for particle therapy, where density variation can strongly affect the dose distribution. We investigated the reliability and reproducibility of our image guided radiotherapy (IGRT) and treatment planning protocol for carbon ion radiotherapy (CIRT) within the phase II mixed beam study (AIRC IG 14300) for the treatment of high risk PCa. In order to calculate the daily dose distribution, a set of synthetic computed tomography (sCT) was generated from the cone beam computed tomography (CBCT) acquired in each treatment session. Planning target volume (PTV) together with rectum and bladder volumes variation were evaluated with sCTs dose-volume histograms (DVH) metrics deviations from the planning values. The correlations between the bladder and rectum volumes, and the corresponding DVH metrics, were also assessed. No significant difference in the bladder, rectum and PTV median volumes between the planning computed tomography (pCT) and the sCT was found. In addition, no significant difference was assessed when comparing the average DVHs and median DVH metrics between pCT and sCT. Dose deviations determined by bladder and rectum filling variations demonstrated that dose distributions were reproducible both in terms of target coverage and organs at risk (OARs) sparing.